Modelos, evidencia y desafíos en la Atención Prehospitalaria: Un análisis global del rol de los equipos de campo en los Servicios de Emergencia Médica Prehospitalarios - Alfaro-Sotomayor, Johann Adrián (2026)
Introduction: The prehospital care field team is the fundamental pillar of the chain of survival in emergency medical systems (EMS). The organization and capacity of these teams vary drastically at the global level, with two main reference models: the Franco-German, led by physicians, and the Anglo-American, based on paramedics.(1,2) These structural differences are accentuated when comparing systems in high-income countries with low- and middle-income countries (LMICs), where prehospital care is often fragmented and lacks resources and qualified personnel.(3) Objective: To conduct a global analysis of the role, importance and models of prehospital intervention teams in the organization, management and effectiveness of EMS,identifying current evidence, systemic challenges and implications for health policy. Methods: A narrative review of the scientificliterature has been carried out, synthesizing studies on the structure, processes and outcomes of prehospital care systems in diverse geographical and economic contexts. Results: Evidence shows that there is no single superior model for all situations.(4) TheFranco-German model allows for advanced on-site interventions, while the Anglo-American model prioritizes rapid transport tothe useful center (“Scoop and Run”).(2,5) The choice of model has profound clinical and economic implications.(2) In LMICs, thelack of organized EMS is a leading cause of preventable deaths, and low-cost improvements, such as basic training andoptimization of dispatch sites, have been shown to reduce mortality.(6.7) System monitoring, interorganizational communication, and resource management are critical factors that modify the quality of care regardless of the model.(8) Conclusion: Optimizing prehospital care requires flexible systems adapted to the local context, rather than the imposition of a single “gold standard”. The main global challenge is to reduce the gap between the advanced models of high-income countries and the precariousness of thesystems in LMICs. The future of EMS depends on the integration of evidence, standardized training, and robust oversight to ensure an efficient and equitable response.